As Spirits Speak: Interaction in Wauja Exoteric Ritual - Christopher Ball (Journal de la Société des Américanistes)
As Spirits Speak: Interaction in Wauja Exoteric Ritual. This paper approaches the connections between ritual and discourse in an Amazonian society through a microanalysis of one instance of talk. I examine a Wauja (Xingu Arawak) ritual session of « bringing spirits », wherein a sick person is aided by a conversation he has with the spirit-monsters that are afflicting him, whom he hopes by virtue of this very conversation to turn from pathogenic to guardian spirits. The conversation is facilitated by a group of representatives from the village, consociates who agree to speak as spirits, and in so doing enter into a contractual relationship of exchange with the sick person and the spirits that involves various obligations and rewards that may span a lifetime, in sickness or in health. In view of the gravity of the circumstance and the weight of the obligation it creates, the ritual interaction is a surprisingly inelaborate and quotidian counterpart to Wauja esoteric shamanic practice and elaborate collective rituals involving music and dance. I question how it is that Wauja ideology supports the practice of regular folk verbally channeling spirits, and suggest that in fact Wauja cultural ideologies of illness, language, and cosmology emerge in precisely such interactive texts as this. The Wauja practice of bringing spirits highlights issues of agency in relation to ritual performativity because it demonstrates how multiple agencies, of persons and spirits, are linked through texts that construct social reality.